CRACKING IN SHEET STRUCTURAL ELEMENT UNDER NON-UNIFORM STRESS FIELD - Sh H HASANOV (Structural Mechanics of Engineering Constructions and Buildings, 2017)
We give a mathematical description of calculation model for cracking in sheet structural element under a non-uniform stress field. The model of pre-fracture zones in state of plastic flow under constant stresses was accepted. The boundary value problem for interaction of zones of weakened interparticle material bonds in the sheet structural element under influence of the inhomogeneous stress field is reduced to a system of singular integral equations. The integral equations further reduce to a system of nonlinear algebraic equations for solution of which we use the method of successive approximations. Sizes of the prefracture zones and limit value of external loads at which in the sheet structural element the cracking occurs are found.